ПІДГОТОВКА ВЧИТЕЛЯ: МЕТОДИКА НАВЧАННЯ ЗАСОБАМИ МУЛЬТИМЕДІЙНИХ ТЕХНОЛОГІЙ (Педагогіка вищої та середньої школи, 2010)
The problem of foreign language teacher's professional training with multimedia technologies is analyzed in the article.